2022
DOI: 10.29303/jppipa.v8i1.1053
|View full text |Cite
|
Sign up to set email alerts
|

Needs Analysis: Development of Character-integrated Problem Solving Model for Chemistry Lessons in Senior High Schools

Abstract: Problem-solving learning models can not only improve cognitive and psychomotor aspects but also affective aspects. One of the affective aspects is character. This study aims to analyze the needs as a basis for developing a character-integrated problem-solving model in high school. This study uses a survey method. The research population is all Senior High School (SMA) and chemistry teachers in Langsa city. The research sample was determined by purposive sampling technique, obtained 4 Senior high schools, along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…For instance, students who solve a problem without considering its aim may have trouble analyzing the sources of information and information outcomes [112]. In addition, Farahian et al [113] investigated how inquiry learners solve an issue through their problem-solving skills, and the findings revealed that inquiry learners identify every potential answer to a problem before making the optimal selection. Investigating the impact of inquiry-based learning on problem-solving skills was recommended in [53,114], despite the paucity of research in this area.…”
Section: Inquiry Learning Style (Ils)mentioning
confidence: 99%
“…For instance, students who solve a problem without considering its aim may have trouble analyzing the sources of information and information outcomes [112]. In addition, Farahian et al [113] investigated how inquiry learners solve an issue through their problem-solving skills, and the findings revealed that inquiry learners identify every potential answer to a problem before making the optimal selection. Investigating the impact of inquiry-based learning on problem-solving skills was recommended in [53,114], despite the paucity of research in this area.…”
Section: Inquiry Learning Style (Ils)mentioning
confidence: 99%
“…Nilai-nilai religious diintegrasikan dalam pembelajaran sebagai hidden curriculum sehingga tercipta generasi unggul, beriman dan berkarakter. Salah satu model pembelajaran yang dapat menyisipkan hiiden curriculum tersebut adalah pembelajaran problem solving terintegrsai karakter (Mauliza et al, 2022). Sasaran Program PKB ini adalah seluruh guru di wilayah NKRI yang tergabung dalam komunitas guru sesuai bidang tugas yang diampu di wilayahnya masing-masing.…”
Section: Pendahuluanunclassified
“…However, students attempting to self-regulate their learning use ineffective strategies and avoid help-seeking behavior ( Lewis and Estis, 2020 ). For example, students solving a problem without thinking about the purpose behind it might face difficulty in evaluating the information sources and information results ( Mauliza et al, 2022 ). Moreover, Farahian et al (2021) examined how inquiry learners solve a problem through their problem-solving skills and the results showed that inquiry learners identify every possible solution to a problem and then make the right and best decision.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%